PEMANFAATAN MEDIA SOSIAL YOUTUBE DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI 1 RETEH RIAU - evi.r. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the background of teachers in utilizing YouTube social media in learning at SMPN 1 Reteh Riau. To determine the practice of utilizing YouTube social media in learning Islamic Religious Education at SMPN 1 Reteh Riau. To determine the contribution of utilizing YouTube social media in increasing students' interest in learning Islamic Religious Education subjects at SMPN 1 Reteh Riau The approach used in this study is to use a descriptive qualitative approach with the Snowball Sampling technique. Data collection techniques used are observation, interviews and documentation. Data are analyzed by reducing data, presenting data and drawing conclusions. Checking the validity of the data using data triangulation techniques. The results of this study indicate that the Background of Teachers in Utilizing Youtube Social Media in Learning at SMPN 1 Reteh Riau consists of three main reasons, the first is that it has become a demand of the times, the second can accelerate student understanding and the third is the flexibility of time and place. Then the practice of utilizing YouTube social media in Islamic Religious Education learning at SMPN 1 Reteh Riau consists of three main steps, the first is preparing computer equipment and ensuring internet network readiness, the second is determining the YouTube link according to the learning material and the third is playing videos and explaining the learning material. Meanwhile, the contribution of utilizing YouTube social media in increasing students' interest in learning in Islamic Religious Education subjects at SMPN 1 Reteh Riau consists of four most noticeable contributions, the first is increasing students' interest in learning, the second is accelerating students' understanding of the material being taught, the third is lightening the teacher's task and the fourth is creating a fun learning atmosphere.